PENGARUH TINGKAT PERTUMBUHAN PERUSAHAAN, RETURN ON ASSETS (ROA), DAN SHAREHOLDER DISPERSION TERHADAP KEBIJAKAN DEVIDEN PADA INDUSTRI MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2011-2013 - Shevina, Amanda Deby; Sulistiyani, Tina (Jurnal Fokus Manajemen Bisnis, 2015)
This research aims to understand the influence of a variable degree growth of the company, return on assets (ROA) and shareholder dispersion partial evaluation and simultaneously to predict dividend policy to companies manufacturing industry which is listed on the Bursa Efek Indonesia. Tekhnik the sample collection by using purposive sampling method of sample and obtained 10 companies. The method of analysis data used a linear regression analysis worship of idols with the level of significance 0.05.The research result show that: 1) the rate of growth of the company have a negative influence and significant against its policies with a value of dividend t count -2,185 and value of significance 0,038. 2) ROA it has some positive effects and significant against its policies with a value of dividend t count 4,287 and value of significance 0,000. 3) shareholder dispersion have a negative influence and significant against its policies with a value of dividend t count -3,420 and value of significance 0,002. 4) the rate of growth of the company, return on asstes (ROA), shareholder dispersion in together influential positive and dignificant for policies with the value of dividend f count 16,089 significance and value 0,000.